Letter from Max Bredig to Marianne and Viktor Homburger, December 20, 1938 - Bredig, Max Albert (1938)
Max Bredig (1902-1977) offers to write an affidavit in support of American immigration visas for his sister Marianne Homburger (1903-1987), and brother-in-law-, Viktor Homburger (1888-1968).
Keywords: Homburger, Viktor, 1888-1968; Homburger, Marianne, 1903-1986; Bredig, Max Albert, 1902-1977; Fajans, Kasimir, 1887-1975; Visas